A Concise Stereoselective Synthesis of Naturally Occurring d‐Xylo‐C18‐Guggultetrol and its C2‐Epimer. Issue 4 (7th March 2019) - Chandra, Naveen; Fernandes, Rodney A.
Abstract: d ‐Gluconic acid δ‐lactone has served as an economical and commercially available key chiral template for a concise 7‐step stereoselective synthesis of d ‐ xylo ‐ and d ‐ lyxo ‐configured guggultetrols. The key steps involved are a one‐pot conversion of d ‐gluconic acid δ‐lactone to γ‐vinyl‐β‐hydroxy‐γ‐lactone, a chain extension through a Grignard reaction and a diastereoselective Sharpless asymmetric dihydroxylation. Abstract : Playing the xylo phone : A concise stereoselective synthesis of D‐ xylo‐ and D‐ lyxo‐ guggultetrols has been achieved from commercially available d ‐gluconic acid δ‐lactone, involving a one‐pot conversion to γ‐vinyl‐β‐hydroxy‐γ‐lactone, chain extension, and a diastereoselective dihydroxylation.